BOOMERANG: A Balloon-borne Millimeter Wave Telescope and Total Power Receiver for Mapping Anisotropy in the Cosmic Microwave Background - Crill, B. P.; Ade, P. A. R.; Artusa, D. R.; Bhatia, R. S.; Bock, J. J.; Boscaleri, A.; Cardoni, P.; Church, S. E.; Coble, K.; deBernardis, P.; deTroia, G.; Farese, P.; et al. (arXiv, 2002)
We describe BOOMERANG; a balloon-borne microwave telescope designed to map the Cosmic Microwave Background (CMB) at a resolution of 10' from the Long Duration Balloon (LDB) platform. The millimeter-wave receiver employs new technology in bolometers, readout electronics, cold re-imaging optics, millimeter-wave filters, and cryogenics to obtain high sensitivity to CMB anisotropy. Sixteen detectors observe in 4 spectral bands centered at 90, 150, 240 and 410 GHz. The wide frequency coverage, the long duration flight, the optical design and the observing strategy provide strong rejection of systematic effects. We report the flight performance of the instrument during a 10.5 day stratospheric balloon flight launched from McMurdo Station, Antarctica that mapped ~2000 square degrees of the sky. : 42 pages, 18 figures, submitted to Ap J, Revised